Pengaruh Promosi Penjualan dan E-service Quality Terhadap Minat Beli Ulang (Studi pada Pembeli di Marketplace Shopee) - Nadya Andika Luthfiana; Sudharto P. Hadi (Universitas Diponegoro, 2019)
The digitalization evolution have caused the rapid growth of the marketplaces. One of them is Shopee, which was the leading marketplace in Southeast Asia and Taiwan. However, Shopee have failed to retain its competitiveness against other marketplaces such as Tokopedia and Lazada with a decrease on its visitor amount who are looking information at Shopee. It indicates that the consumer’s interest rate are fairly low which will affect repurchase intention. Therefore, Shopee need to pay attention for the possible affecting conditions related to consumers purchasing intentions. This study aims to determine the effect of sales promotion and also e-service quality on Shopee consumers purchasing intentions. This type of research is explanatory research. Samples are taken from 100 respondents who had made purchases on Shopee. The sampling techniques are accidental sampling and purposive sampling. Data were collected by a questioner, and literature studies. The analysis methods used are validity test, reliability test, correlation test, simple linear regression test, multiple linear regression test, determination coefficient (R2), and significance t test and f test with the help of IBM SPSS program version 25.0. Based on the results of the analysis, it can be concluded that the sales promotion and e-service quality have an effect on purchasing intentionss proven through the simple regression test with the result in regression values of 0,690 and 0,785.The given advice to the company are to fix the promotion issues and improving the amount of the selling promotion that have been carried and also re-evaluate the e-service quality strategy.